Sastra Diasporik?: Suara-Suara Tionghoa Baru di Indonesia - Pamela Allen (Antropologi Indonesia, 2003)
Since the 'beginning' of modern Indonesian literature in the early twentieth century, Indonesian writers have engaged with the project of defining Indonesian identity. Most serious writers engaged both with the mission of creating a new literature and with the project of interrogating and investigating issues of national identity. It is a mission which continues to inform Indonesian literature in the twenty first century. Literature written by peranakan Chinese flourished at the end of the nineteenth century and the early twentieth century. But because the first language of these peranakan writers was low or 'market' Malay, much of it received scant attention from Indonesian critics, who reserved their praise for writing in the court-derived high Malay favored by the recognized publishing houses. Peranakan literature reached its zenith in the 1920s and 1930s-whichwas also a time of heightened Chinese nationalism in Java. Thanks to the meticulous work of two scholars in particular-Claudine Salmon and Leo Suryadinata-much of this early writing has now been documented and critically analyzed. However, Salmon and Suryadinata's commentary effectively ends at 1965. Chinese-Indonesians who did continue to write during the New Order on the whole projected themselves and were constructed by others as 'Indonesian'. They thus assimilated as writers as they did as citizens, and their ethnicity never featured as part of their work. The category 'Chinese-Indonesian literature' for all intents and purposes ceased to exist. It was subjected to the same process of erasure as Chinese ethnicity. Since the fall of Soeharto Chinese-Indonesian writers have begun to write as Chinese-Indonesians, some using their Chinese names, some writing in Mandarin. This paper begins to fill a significant gap in documenting the ways in which recent literary works by Chinese-Indonesians give expression to their understanding of themselves and their place in the Indonesian nation-state.